Análisis petrogenético de las rocas volcánicas de la isla de providencia en el caribe colombiano (1995)
The geochemical characteristics of the volcanic rocks present at the Providencia Island  show that these do not be created from a comagmatic  processes of fractionated crystallization.  It is demostrated that in its genesis were involucrated different geotectonical setting, according with the major and trace elements analysis.